Breast lipoma with central fat necrosis: case report - Bouroumane, Mohamed Reda (Pan Afr Med J, 2016)
Fat necrosis of the breast is a benign non-suppurative inflammatory process of adipose tissue that most commonly occurs as the result of minor breast trauma. We present a case of a 40-years-old female with fat necrosis in a breast lipoma. She presented with an overlapping mass on the lateral quadrants. Mammography showed Well delineated radiolucent mass with peripheral “egg-shell” calcifications, that appeared an hypoechoic mass with posterior shadowing on ultrasonography. A history of accidental trauma raises the suspicion of fat necrosis. Pathology is necessary when radiological findings simulate malignancy.